Privatisation, current issues : a study of recent privatisation in Argentina, Brazil, Mexico and Venezuela and, by way of comparison, the current programmes underway in France, Italy and the United Kingdom /: a study of recent privatisation in Argentina, Brazil, Mexico and Venezuela and, by way of comparison, the current programmes underway in France, Italy and the United Kingdom. (2001) - Unknown
No abstract available